2019
DOI: 10.3390/su11072090
|View full text |Cite
|
Sign up to set email alerts
|

The Effects of Co-Residence on the Subjective Well-Being of Older Chinese Parents

Abstract: The purpose of this study was to examine the effects of co-residence on the parental subjective well-being among older Chinese parents. Our analysis included 2968 elderly parents. Parental subjective well-being was stratified into positive well-being (PWB) and negative well-being (NWB). Positive well-being was assessed through questions about life satisfaction, optimism, and happiness and NWB was measured by questions about fear, loneliness, and feelings of uselessness. We found co-residence with adult childre… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
10
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 7 publications
(11 citation statements)
references
References 48 publications
(91 reference statements)
1
10
0
Order By: Relevance
“…(1) * p < 0.1, ** p < 0.05, ** p < 0.01 (2) Dependent variable of health is an order category variable of subjective health (5 5 excellent, 4 5 very good, 3 5 good, 2 5 fair, 1 5 poor) (health 5 1, no 5 0). The order logit model is used (3) The control variables including age, education, married, urban, household income and smoker dummy variables are estimated, but these results are not shown in Table 4 (4) Basic model: variable in survey year (t period) is used; LVtÀ1: lagged variable in tÀ1 period is used; LVtÀ2: lagged variable in tÀ2 period is used Source(s): Calculated based on CHARLS 2011-2015 For an explanation of the SP-MH-SRH channel, Chou et al (2006), Chen and Short (2008), Miao and Wu (2019), Zhu et al (2019) and Matsuura and Ma (2020) reported that living alone may negatively affect well-being (co-residence with children may increase the well-being of parents). It can be considered that communication with others by participating in social activity may reduce the impact of being emotionally alone, particularly for single-person elderly households, which may improve the health status of the elderly.…”
Section: Results Of the Channels Of The Impact Of Sp On Health Statusmentioning
confidence: 99%
See 1 more Smart Citation
“…(1) * p < 0.1, ** p < 0.05, ** p < 0.01 (2) Dependent variable of health is an order category variable of subjective health (5 5 excellent, 4 5 very good, 3 5 good, 2 5 fair, 1 5 poor) (health 5 1, no 5 0). The order logit model is used (3) The control variables including age, education, married, urban, household income and smoker dummy variables are estimated, but these results are not shown in Table 4 (4) Basic model: variable in survey year (t period) is used; LVtÀ1: lagged variable in tÀ1 period is used; LVtÀ2: lagged variable in tÀ2 period is used Source(s): Calculated based on CHARLS 2011-2015 For an explanation of the SP-MH-SRH channel, Chou et al (2006), Chen and Short (2008), Miao and Wu (2019), Zhu et al (2019) and Matsuura and Ma (2020) reported that living alone may negatively affect well-being (co-residence with children may increase the well-being of parents). It can be considered that communication with others by participating in social activity may reduce the impact of being emotionally alone, particularly for single-person elderly households, which may improve the health status of the elderly.…”
Section: Results Of the Channels Of The Impact Of Sp On Health Statusmentioning
confidence: 99%
“…At the same time, urbanization and economic development lead to more elderly single-person households (Matsuura and Ma, 2020). It has been pointed out that living alone may negatively affect the well-being of the elderly (Chou et al, 2006;Chen and Short, 2008;Miao and Wu, 2019;Zhu et al, 2019;Matsuura and Ma, 2020). Social participation is expected to improve the health status of elderly living in single-person households (Won and Kim, 2020).…”
Section: Discussionmentioning
confidence: 99%
“…In year 2016, the percentage of Hong Kong elders living with adult children became lower than 50.0% [48]. By studying sample of Mainland Chinese elders, researchers revealed that the proportion of respondents who coresided with an adult child declined by around 10.0% from 2008 to 2011 [49]. Xu's study [50] showed that the percentage of seniors living with their sons decreased, but the proportion of seniors living with daughters increased.…”
Section: Changing Patterns Of Living Arrangements Among Older Adultsmentioning
confidence: 99%
“…Another study by Zeng et al ( 2016 ) documented that having daughters was more beneficial than having sons in terms of the health outcome of older parents. Furthermore, recent studies have found that, even in patriarchal societies such as China, living with daughters is associated with greater happiness of older parents (Yuan et al, 2021 ), or that co-residence with sons as well as co-residence with daughters are beneficial to parents’ subjective wellbeing (Zhu et al, 2019 ).…”
Section: Introductionmentioning
confidence: 99%
“… 1 Based on our literature search, we didn’t find any study that methodologically corrected for sex-selective abortion related biases and how that affects research on children’s gender and parental happiness in China. The only two studies that corrected for possible selection bias—Yuan et al ( 2021 ) and Zhu et al ( 2019 )—limit the focus to inter-generational co-residence status. …”
mentioning
confidence: 99%